ANALISIS YURIDIS TERHADAP SANKSI HUKUM PIHAK YANG TIDAK MEMILIKI HAK ASUH ANAK DALAM SUATU PUTUSAN PERCERAIAN - Djafar, Sri Mitta Aisha; Junus, Nirwan; Bakung, Dolot Alhasni (Jurnal Hukum Ius Publicum, 2025)
This study analyzes legal sanctions against parties who do not comply with court decisions in post-divorce child custody cases. The main focus is to identify legal sanctions that can be applied in accordance with the laws and regulations in Indonesia, as well as to examine the inhibiting factors that cause non-compliance with court decisions. The results show that although child custody is expressly regulated in legal regulations such as the Marriage Law and the Compilation of Islamic Law, there are significant challenges in the implementation of judgments, especially when it comes to emotional aspects and protection of children. Hindering factors include ignorance of the law, conflicts between the parties to the dispute, and a lack of a firm law enforcement system. This study recommends strengthening enforcement mechanisms and increasing legal awareness to ensure the effective implementation of child custody.